(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
To the article: "Modeling of pressure movements of the mixture in the pipelines of engineering structures" A uniform pressure flow of a dispersed mixture of water and suspended sediments is considered. The movement of the mixture in a round cylindrical tube is turbulent. An equation for the pressure movement of the mixture is given and the hydraulic parameters of the mixture are found.